2013
DOI: 10.1089/brain.2012.0117
|View full text |Cite
|
Sign up to set email alerts
|

Thalamus, Brainstem and Salience Network Connectivity Changes During Propofol-Induced Sedation and Unconsciousness

Abstract: In this functional magnetic resonance imaging study, we examined the effect of mild propofol sedation and propofol-induced unconsciousness on resting state brain connectivity, using graph analysis based on independent component analysis and a classical seed-based analysis. Contrary to previous propofol research, which mainly emphasized the importance of connectivity in the default mode network (DMN) and external control network (ECN), we focused on the salience network, thalamus, and brainstem. The importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 68 publications
11
96
0
Order By: Relevance
“…A reduction in the coherence and information transfer among select frontal, parietal, and occipital cortical regions has been found using electrophysiological techniques (Ku et al, 2011;Lee et al, 2009bLee et al, , 2013. More generally, anesthetics have been thought to target subcortical mechanisms (Brown et al, 2010;Guldenmund et al, 2013;Mhuircheartaigh et al, 2010) including the natural sleep promoting circuits (Franks and Zecharia, 2011;Zecharia and Franks, 2009), and the neocortex itself (Hentschke et al, 2005;Hudetz, 2006;Seth et al, 2005;Velly et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A reduction in the coherence and information transfer among select frontal, parietal, and occipital cortical regions has been found using electrophysiological techniques (Ku et al, 2011;Lee et al, 2009bLee et al, , 2013. More generally, anesthetics have been thought to target subcortical mechanisms (Brown et al, 2010;Guldenmund et al, 2013;Mhuircheartaigh et al, 2010) including the natural sleep promoting circuits (Franks and Zecharia, 2011;Zecharia and Franks, 2009), and the neocortex itself (Hentschke et al, 2005;Hudetz, 2006;Seth et al, 2005;Velly et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Subcortical ROIs were as follows: hippocampus (Hipp), caudate-putamen (CPu), nucleus basalis of Meynert (NBM), medial thalamus (mTh), hypothalamus (Hypo), and nucleus pontis oralis (PnO). The ROIs were chosen to cover the most extensive cortical regions and important subcortical centers suggested to be involved in the anesthetic modulation of the ascending arousal system (Alkire et al, 2007;Brown et al, 2010;Devor and Zalkind, 2001;Guldenmund et al, 2013;Mhuircheartaigh et al, 2010;Sukhotinsky et al, 2007;Zecharia and Franks, 2009). Group analysis for 12 ROIs involved the calculation of CTC temporal variance at each propofol dose and the relative contribution of each ROI to the dose-dependent change in global variance.…”
Section: Brain Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…With task-free neuroimaging, an examiner is not dependent on patient co-operation and a patient's possibility to exhibit body movement. In resting state fMRI, examination of intactness of the default mode network (DMN) might improve diagnosis in DOC, as it is known to be important for internally-oriented consciousness [5,[7][8][9][10][11][12]. In recent years, interest has also increased for other brain regions associated with specific higher-order networks [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the DMN connectivity has been shown to be decreased in deep sleep (Horovitz et al, 2009), general anesthesia (Boveroux et al, 2010;Guldenmund et al, 2013), and in patients in coma, vegetative state/unresponsive wakefulness syndrome (VS/UWS) , and minimally conscious state (MCS) (Vanhaudenhuyse et al, 2010). Anesthesia studies have also specifically focused on the posterior cingulate cortex (PCC)/precuneus, showing propofol-induced alterations of the connectivity pattern (Amico et al, 2014;Liu et al, 2014;Stamatakis et al, 2010), while others indicated the involvement of a wide range of higher-order RSNs in the loss of responsiveness (expected to be a state of unconsciousness), like the external control network (ECN; left and right ECN components are frequently mentioned separately), important for externally oriented awareness (Boveroux et al, 2010;Liu et al, 2012), and the salience network, which is implicated in the detection of salient stimuli (Guldenmund et al, 2013). Furthermore, disconnection between higherorder RSNs and the thalamus has been found to be associated with propofol-induced loss of responsiveness (Boveroux et al, 2010;Guldenmund et al, 2013;Liu et al, 2013).…”
mentioning
confidence: 99%